Decentralization and quality assurance in the Ugandan primary education sector - Abu-Baker, Mutaaya Sirajee (Rhodes University, Faculty of Education, Department of Education, 2018)
The study presented in this thesis is a case study analysis of decentralization and quality assurance in a decentralized set up of the Ugandan Primary Schooling. The research looked at how the monitoring and evaluation informed the policy formulation process to regulate quality assurance in a decentralized governance of primary education. The Study was positioned in the critical realist paradigm, interpretive in orientation and used both coding and thematic techniques to understand the teachers', SMC members', and officers' (at district and ministry levels) experiences and perceptions of quality assurance in a decentralized set up. Data was gathered using interviews, document analysis and observation methods. The findings indicated that the study was affected by eleven themes: Management System and Leadership, Human Resource Management, Finance Administration and Management, Parenting and Nutrition, Politics, Motivation, Social Structures and Patterns, Legislative Process and Policies, Infrastructure Development and Management, Community Involvement in Education and Curriculum and Professionalism. The monitoring and evaluation system had a framework in which it operates, though there was no quality assurance policy to guide the provision of quality education. The study finally indicated that there are more threats in a decentralized set up that put Quality in danger. Secondly, there was absence of supervision/inspection in schools as there was no evidence to prove this due to absence of reports. However, document analysis indicated visits of officers to schools. Records management was a problem to schools. Decentralization was adopted at different levels by different countries to address specific problems identified in view of service delivery. Finally, though monitoring and evaluation results informed the policy and decision makers, there was no quality assurance policy to guide the provision of quality education in institutions.
Keywords: Schools -- Decentralization -- Uganda; Education, Primary -- Uganda; Educational change -- Uganda